Lamin B autoantibodies in sera of certain patients with systemic lupus erythematosus (The Rockefeller University Press, 1987)
Sera from four patients with systemic lupus erythematosus containing antibodies that yield nuclear rim staining of HEp-2 cells by indirect immunofluorescence were identified and characterized. Each serum contained autoantibodies reacting strongly with lamin B on western blots. One of the four sera displayed weaker reactivity with lamins A and C, while the other three displayed only minimal reactivity with lamins A and C. Titers of antilamin antibodies ranged from 1:1,250 to 1:36,250. Two of the sera also reacted at a dilution of 1:20 with cytoplasmic filaments of PTK-2 cells, suggesting that a small fraction of the autoantibodies in these sera may bind to alpha-helical domains of the lamins that are homologous to those of intermediate filaments. The majority of the antilamin antibodies in these patients' sera are specific for portions of the lamin B molecule that are not homologous to lamins A and C, however. The findings suggest that autoantibodies to the nuclear lamina may, in some instances, be responsible for a rim pattern in the fluorescent antinuclear antibody assay. In addition, autoantibodies to the nuclear lamina in sera of certain patients with systemic lupus erythematosus may be useful for defining the molecular structure and biological functions of lamin B, as well as for studying mechanisms of autoimmunity.